Bis(dinitropyrazolyl)methanes as Stable High Energy Materials - Kim, Myeong Hak; Lee, Byeongil; Kim, Namtae; Shin, Moonyong; Shin, Hye Jung; Kwon, Kuktae; Kim, Jin Seuk; Lee, Sung Kwang; Kim, Young Gyu (Bulletin of the Korean Chemical Society, 2017)
The development of high energy materials (HEMs) with both high explosive performance and decreased sensitivity is a main theme of current research for energetic materials. Polynitroazoles are good building blocks for new energetic materials because of their stable chemical properties. Two new bis(dinitropyrazolyl)methanes as potential insensitive HEMs were prepared via either the coupling of dinitropyrazole or the nitration of bis(mononitropyrazolyl)methane. Their insensitive properties are also reported and compared to those of RDX (trinitrohexahydro‐s‐triazine) and HNIW (CL‐20, hexanitrohexaazaisowurtzitane).